1997
DOI: 10.1006/jcph.1996.5594
|View full text |Cite
|
Sign up to set email alerts
|

Perfectly Matched Absorbing Layers for the Paraxial Equations

Abstract: the 15 degree approximation. The formulation of the problem is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 9 publications
1
66
0
Order By: Relevance
“…Considering (15) as an equation in the frequency x for a given value of the wave vector k, we obtain four solutions …”
Section: Harmonic Plane Waves and Slowness Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering (15) as an equation in the frequency x for a given value of the wave vector k, we obtain four solutions …”
Section: Harmonic Plane Waves and Slowness Diagramsmentioning
confidence: 99%
“…[11,12,28,37,39]). The method has been extended to various propagation models (the paraxial wave equations [15], the linearized Euler equations [22,24,32], etc. ), including in particular elastic wave propagation in isotropic [21] and anisotropic media [17].…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the transparent boundary conditions on Γ ⊥ from a numerical point of view, the so called Perfectly Matched Layers (PML) approach leads to a very efficient method which has been proposed for Schrödinger equation in [17]; this method has also been implemented in the numerical code HERA (cf. [3]), with which the following numerical results are obtained.…”
Section: Numerical Schemementioning
confidence: 99%
“…Collino [10] showed that the PML can be interpreted as a change of variable in the complex plane. The change of variable results in a simple modification of the differential operator a 'iW a %+ iu + a(z) z"…”
Section: Perfectly Matched Layer4mentioning
confidence: 99%
“…encoding parm Chirp encoding requires a stretching parameter which may vary between the approximate range [2][3][4][5][6][7][8][9][10]. Linear phase encoding requires the desired time shift between the shots, -to,in seconds.…”
Section: Salvo User's Guide -mentioning
confidence: 99%